Synthesis and Antimicrobial Activity of 8-Alkyl Coptisine Derivatives - Jiang, Xiao-Fei; Ye, Xiao-Li; Zhang, Baoshun; Li, Xue-Gang; Liu, Xingyan (Asian Journal of Chemistry, 2011)
The compounds 8-butyl (2), 8-hexyl- (3), 8-octyl- (4), 8-decyl (5) and 8-dodecylcoptisine chloride (6) were synthesized and their antimicrobial activities were tested in vitro. LD50 were tested by mice's abdominal cavity injection in order to evaluate their structure-activity relationships. The results indicated that the derivatives exhibited high antimicrobial activities than coptisine, especially against Gram-positive bacteria and fungi. The 8-octylcoptisine displayed the highest antimicrobial activity in all compounds. The toxicity of compounds 2-6 was stronger than that of coptisine. However, upon elongating the aliphatic chain, the toxicity decreased gradually.